Microglial Dysfunction and Cognitive Impairment in Animal Models of Type 2 Diabetes: A Systematic Review Bridging Diabetes and Early-Stage Neurodegeneration - Aranđelović Ilić, Jovana; Đuretić, Jasmina (Archives of Pharmacy, 2026)
Type 2 diabetes (T2D) is closely associated with cognitive impairment and an increased risk of dementia. Early neuropathological alterations in T2D are increasingly considered to involve neuroinflammatory processes, suggesting that microglial function in the diabetic brain may be compromised or shifted towards a maladaptive activated state. Growing evidence implicates microglial dysfunction as a key mechanism underlying T2D-related cognitive impairment. Alterations in spatial learning, memory, and executive function are accompanied by functional and phenotypic changes in microglial cells, particularly within hippocampal and cortical circuits. At the same time, early neurodegenerative changes occur, including neuronal loss, synaptic alterations, accumulation of Aβ and p-Tau, and Alzheimer’s disease (AD)-related transcriptomic signatures in vulnerable brain regions. With aging, microglia contribute more significantly to neurodegeneration as their regulatory interactions with neurons weaken, favoring sustained activation. This mini systematic review aims to synthesize current in vivo evidence on the relationship between cognitive impairment and microglial alterations in animal models of T2D and to delineate the underlying pathophysiological mechanisms linking chronic metabolic stress, microglial dysfunction, and early neurodegenerative changes. Furthermore, it seeks to highlight how these mechanistic pathways, encompassing microglial signaling, inflammatory mediators and metabolic reprogramming, may represent promising therapeutic targets for preventing or attenuating diabetes-associated neurodegeneration.